DETERMINATION OF MARKETING STRATEGY AT WARUNG LESEHAN AA REMBANGAN USING SWOT ANALYSIS - Kuncoro, Muh Alfan; Sari, Maheni Ika; Wibowo, Yohanes Gunawan (Jurnal Warta Dharmawangsa, 2025)
In the era of increasingly fierce business competition, especially in the culinary sector, the management of an effective marketing strategy is the main key to maintaining and developing the business. Warung Lesehan AA Rembangan as one of the traditional culinary business actors faces the challenge of staying relevant and competitive amid many competitors and changing consumer preferences. This study aims to analyze the internal and external factors that affect the marketing strategy of Warung Lesehan AA Rembangan and formulate an effective business development strategy based on SWOT, IFE (Internal Factor Evaluation), and EFE (External Factor Evaluation) analysis. The research method used is a descriptive study with a qualitative and quantitative approach through the collection of primary and secondary data. The results of the analysis show that the main strength of Warung Lesehan AA lies in active promotion through discounts and banners as well as an easy-to-reach strategic location. However, there are weaknesses in the form of simple and less modern stall facilities that have the potential to reduce the comfort of visitors. The main threat faced is the stiff competition with the number of lesehan stalls in the Rembangan area. Based on the results of the SWOT analysis, it is recommended to implement growth strategies that maximize strengths and opportunities, as well as weakness improvement strategies to deal with existing threats. This research provides practical recommendations for the managers of Warung Lesehan AA to improve the quality of services, facilities, and promotional innovations to strengthen the competitiveness and sustainability of the business.